Pengaruh Harga dan Kualitas Produk terhadap Keputusan Pembelian Kain Tenun Prana Sutra di Desa Kalianget - Maharani, Ida Ayu Made Novita; Suwendra, I Wayan (Jurnal Pendidikan Ekonomi Undiksha, 2025)
The purpose of this research is to determine (1) the influence of price on the decision to purchase Prana Sutra woven fabric in Kalianget Village (2) the influence of product quality on the decision to purchase Prana Sutra woven fabric in Kalianget Village (3) the influence of price and product quality on the decision to purchase woven fabric Prana Sutra in Kalianget Village. The type of research used is causal research. The sampling technique used is accidental sampling. The population of this research is every individual who has purchased woven fabric products at the Prana Sutra boutique in Kalianget Village with a sample size of 96. The data collection method uses a questionnaire and is analyzed using multiple linear regression. The research results show that (1) there is a positive and significant influence of price on the decision to purchase Prana Sutra woven fabric in Kalianget Village partially, with a significance value of 0.000 < 0.05. (2) there is a positive and significant influence of product quality on the decision to purchase Prana Sutra woven fabric in Kalianget Village partially, with a significance value of 0.000 < 0.05. (3) there is a positive and significant influence between price and product quality on the decision to purchase Prana Sutra woven fabric in Kalianget Village simultaneously, with a significance value of 0.000 < 0.05. The magnitude of the influence of price and product quality on purchasing decisions is 38.9%, as evidenced by the coefficient of determination value of 0.389.